2020
DOI: 10.21203/rs.3.rs-42561/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns of coronal and sagittal deformities in adolescent idiopathic scoliosis

Abstract: Background: Thoracic scoliosis has been shown to be associated with hypokyphosis in adolescent idiopathic scoliosis (AIS). However, the relationship of sagittal spino-pelvic parameters with different coronal curve patterns and their influence on patient-perceived quality of life is unknown. This study aims to determine the association between coronal and sagittal malalignment in patients with AIS and to determine their effects on SRS-22r scores. Methods: A cross-sectional study was conducted on 1054 consecutiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…[21] In contrast, some studies have shown that LL in AIS were similar to those in the normal adolescents and shown that LL within the normal range were also similar among different types of scoliosis. [37] The mild and moderate scoliosis were recruited in this study, and we found that type I was the most common in mild scoliosis, followed by type III and type II. However, type II and type III were most common in moderate scoliosis.…”
Section: Coccygeal Morphology In Patients With Different Types Of Sco...mentioning
confidence: 86%
“…[21] In contrast, some studies have shown that LL in AIS were similar to those in the normal adolescents and shown that LL within the normal range were also similar among different types of scoliosis. [37] The mild and moderate scoliosis were recruited in this study, and we found that type I was the most common in mild scoliosis, followed by type III and type II. However, type II and type III were most common in moderate scoliosis.…”
Section: Coccygeal Morphology In Patients With Different Types Of Sco...mentioning
confidence: 86%